William Shakespeare A Study of the Poet and Five Famous Contemporaries who between them used the Rune Ciphers to reveal his True Identity - Roper, David L. (Journal of Scientific Exploration, 2017)
A presentation of facts that have caused Shakespeare's identity to be questioned. New evidence is presented which indicates that Shakespeare's real identity was an open secret protected by strict censorship. This caused those most concerned - colleagues of the man behind the penname Shakespeare -  to reveal the truth in a number of Cardano grilles—these being the latest invention for concealing secret information. All grilles were constructeed by eye witnesses at the time, and whose names are known to the historical literature of that age. Each grille contains the same codeword used by the encoders, and the result has been subjected to a probability test for a chance occurrence. The results confirm that the chance was not involved.